Heterogeneidad lingüística en La vorágine - Portilla, Mario (2014)
In The Vortex, José Eustasio Rivera proposes a political project for the configuration of the Colombian nation, which seeks the incorporation of the most eastern part of this country, lengthily forgotten by the government authorities. Nevertheless, this project seems not to include every citizen in the same way. This article analyzes the explicit representations of the roman characters and the stereotypical characterization of their discourse, making clear the ideology of the writer.